Neuroblast-Like Cell Culture Derivation from Newborn Piglet Adrenal Glands Using Selective Adhesion Method - Plaksina, Ekaterina M.; Sidorenko, Olga S.; Legach, Eugeniy I.; Bozhok, Galina A. (Problems of Cryobiology and Cryomedicine, 2016)
Probl Cryobiol Cryomed 2016; 26(2):188.